Cover Image. Issue 9 (21st September 2018) - Liu, P.; Fan, Y.; Wei, Y.; Zeng, F.; Li, R.; Fei, N.; Qin, W.
Abstract : The cover image, by P. Liu et al., is based on the Original Article Altered structural and functional connectivity of the insula in functional dyspepsia, DOI:10.1111/nmo.13345 .